2014
DOI: 10.1542/peds.2013-0426
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Recurrence of Group B Streptococcal Late-Onset Sepsis in Twins

Abstract: Group B Streptococcus (GBS) remains the leading cause of neonatal sepsis and meningitis in industrialized countries. Whereas the use of intrapartum antibiotic prophylaxis has led to a significant decline in early-onset sepsis, the incidence of late-onset sepsis has remained unchanged. Whether late-onset sepsis usually originates from established mucocutaneous GBS colonization of the infant or whether it results from an acute exogenous GBS infection remains controversial. Here we report on twins who both twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 16 publications
0
18
0
8
Order By: Relevance
“…44 Most of the studies (17/22) reported clusters occurring in neonatal intensive care units (NICUs) or special care nurseries; the remainder described clusters occurring in or originating from maternity units in regional, district or community hospitals. There were two reports of LOD in twins 35 and triplets 38 and two references describing clusters only of EOD 23 , 34 (see supplementary files). The other reported clusters involved LOD ( n = 12) or a mix of early and LOD ( n = 6) as described below.…”
Section: Neonatal Gbs Disease Clustersmentioning
confidence: 99%
“…44 Most of the studies (17/22) reported clusters occurring in neonatal intensive care units (NICUs) or special care nurseries; the remainder described clusters occurring in or originating from maternity units in regional, district or community hospitals. There were two reports of LOD in twins 35 and triplets 38 and two references describing clusters only of EOD 23 , 34 (see supplementary files). The other reported clusters involved LOD ( n = 12) or a mix of early and LOD ( n = 6) as described below.…”
Section: Neonatal Gbs Disease Clustersmentioning
confidence: 99%
“…GBS is a well-established cause of soft tissue and bone infections, both in infants and adults (32,33). In the dermis, an important barrier against soft tissue infections caused by streptococci, resident dermal MFs constitute the main immune cell population (34).…”
Section: Dermal Mfs Require Endosomal Tlr13 For Sensing Of Gbsmentioning
confidence: 99%
“…Intradermal injection in the ear pinna of WT mice results in neutrophil recruitment and resolution of infection that are dependent on the presence of dermal MFs (3). This model is relevant for GBS, because local infections of skin and soft tissue often precede neonatal GBS sepsis (32). To verify the importance of TLR signaling, we used MyD88 2/2 mice, which are severely impaired in the sensing of surface and endosomal TLRs.…”
Section: Unc-93b (3d) Mice Incompletely Control Dissemination Of Gbs mentioning
confidence: 99%
“…Next to the lethality of GBS meningoencephalitis (5–10%), long‐term neurologic impairment of variable degrees affects up to 30 to 70% of surviving infants . GBS has been cultured from breast milk of the nursing mother and the intestinal tract of individual infants before onset of LOD and meningitis in individual cases, which suggests that GBS is acquired through the intestinal route, yet this model remains somewhat speculative. The concept that GBS dissemination happens from the intestine to the CNS is supported by the study of Poyart et al., where intestinal GBS colonization in mice in the first three weeks of life led to CNS invasion and meningoencephalitis .…”
Section: Introductionmentioning
confidence: 99%